PEMANFAATAN PLATFORM MERDEKA MENGAJAR (PMM) DALAM MENGEMBANGKAN KOMPETENSI PEDAGOGIK GURU DI SD NEGERI 182 PEKANBARU - Dwi Yulia Ummairoh; Zaka Hadikusuma Ramadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Independent Teaching Platform (PMM) is a system developed by the government to support increasing teacher competency. This platform includes a digital platform that contains various content related to the Independent Curriculum. This research was conducted to find out how the Merdeka Mengajar Platform (PMM) is used in developing teacher pedagogical competence at SD Negeri 182 Pekanbaru. This research uses qualitative research with a narrative approach. The source of this research is the principal and teachers at SD Negeri 182 Pekanbaru. Data was collected using interviews, observation and documentation methods. Using data analysis techniques, namely data reduction, data presentation, drawing conclusions and verification. The results of this research show that the Merdeka Mengajar Platform (PMM) can help teachers develop their pedagogical competencies. By utilizing various features in PMM teachers can develop competencies, create learning program designs, asses or evaluate students, find inspiration from inspirational videos and create practical works or ideas.   Keywords: teacher pedagogical competence, elementary education, the independent teaching platform